2016
DOI: 10.1111/cns.12588
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Stimulates the SIRT1/Nrf2 Signaling Pathway Counteracting Lipopolysaccharide (LPS)‐Induced Oxidative Stress to Rescue Postnatal Rat Brain

Abstract: SUMMARYAims: Lipopolysaccharide (LPS) induces oxidative stress and neuroinflammation both in vivo and in vitro. Here, we provided the first detailed description of the mechanism of melatonin neuroprotection against LPS-induced oxidative stress, acute neuroinflammation, and neurodegeneration in the hippocampal dentate gyrus (DG) region of the postnatal day 7 (PND7) rat brain. Methods: The neuroprotective effects of melatonin against LPSinduced neurotoxicity were analyzed using multiple research techniques, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(145 citation statements)
references
References 56 publications
11
129
0
Order By: Relevance
“…We believe that the beneficial effect of antenatal maternally administered melatonin on fetoplacental hemodynamic changes caused by IUI‐induced oxidative stress occurred because melatonin reduced the pro‐inflammatory and oxidative stress mediators by promoting the anti‐inflammatory SIRT1/Nrf2 pathway . We showed that melatonin reduced oxidative stress markers, 4‐HNE, as well as pro‐inflammatory mediators and that melatonin activated the gene expression of SIRT1, Nrf2, and HO‐1 in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the beneficial effect of antenatal maternally administered melatonin on fetoplacental hemodynamic changes caused by IUI‐induced oxidative stress occurred because melatonin reduced the pro‐inflammatory and oxidative stress mediators by promoting the anti‐inflammatory SIRT1/Nrf2 pathway . We showed that melatonin reduced oxidative stress markers, 4‐HNE, as well as pro‐inflammatory mediators and that melatonin activated the gene expression of SIRT1, Nrf2, and HO‐1 in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS quantification assay in the brain homogenates of all treated groups was conducted as reported earlier in the literature and by our research group [28, 29] with slight modification. Briefly, the brain homogenates from the respective groups were diluted 1:20 times with Locke’s buffer (ice-cold) to get 5 mg tissue/ml concentration.…”
Section: Methodsmentioning
confidence: 99%
“…BCA proten assay kit (Bioworld, USA) to estimate total protein level of TBS-, TBSX-, and FA-. Equal quantities of protein extracts were subjected to SDS-PAGE for western blotting and transferred to polyvinylidene difluoride membranes (PVDF) membranes (Millipore, USA) [49]. The membranes were incubated at 4°C overnight with anti -Nrf2 (1:1000, Biolegend, USA) primary antibody after blocking in 5% non-fat milk for 1 hour at room temperature.…”
Section: Western Blotmentioning
confidence: 99%